PENGARUH NAUNGAN TERHADAP KANDUNGAN KLOROFIL DAUN DAN HASIL DUA VARIETAS TANAMAN KEDELAI (Glycine max L. Merill) (The Effect of Shade on Chlorophyll Content and the Yield of Two Soybean Varietes (Glycine max L. Merill)) - Novi Novita; Nerty Soverda; . Gusniwati (Bioplantae, 2012)
This study aimed to investigate the effect of shade on leaf chlorophyll content and the yield of two soybean varieties. The experiment was conducted at the Experimental Farm of Faculty of Agriculture, University of Jambi, located in the Village District Mendalo Jambi. Experiments using split plot design (Split-Plot Design) by 2 factors: the first factor as the main plot is a shade (N) consisting of 2, ie, without shade and 50% shade. The second factor is the subplot soybean varieties (V) consisting of varieties Petek (tolerant) and Jayawijaya (sensitive). The variables measured were plant height, chlorophyll and total weight of 100 grains, while the number of pods per plant, number of pods per plant contains, and the yield per plant showed no significant differences. Petek varieties tend to show tolerance to shade melelui increase in the number of total chlorophyll a dam to increase the weight of 100 grains were higher than Jayawijaya.Keywords: Soybean, shade, leaf chlorophyll